A NEW INNOVATIVE APPROACH TO PUBLIC PROCUREMENT (Global Conference on Multidisciplinary Research and Innovation, 2026)
Large-scale reforms aimed at digitalizing the public procurement system are continuing in New Uzbekistan. Through electronic tendering, online auctions, and e-marketplace platforms, significant results have been achieved in ensuring the efficient use of budgetary funds, reducing the influence of the human factor, and limiting corruption risks. However, at present, the most pressing issue remains the transformation of public procurement from a simple electronic system into an intelligent management system.